Bicycle route preference and pollution inhalation dose: Comparing exposure and distance trade-offs. Issue 1 (March 2016) - Bigazzi, Alexander Y.; Broach, Joseph; Dill, Jennifer
Abstract: Do bicyclist preferences for low-traffic facilities lead to route choices that minimize air pollution inhalation doses? For both preferences and doses a routing trade-off can exist between exposure to motor vehicle traffic and trip duration. We use past studies of bicycle route preferences and pollution exposure levels to estimate exposure/distance trade-offs among roadway facility types. Exposure/distance trade-offs for preferences and doses are found to be similar when comparing off-street paths, bike boulevards, and low-to-moderate traffic streets with or without bike lanes; when choosing a route among these facilities we expect bicyclists to approximately minimize inhalation doses. Compared to dose-minimizing behavior, bicyclists tend to use high-traffic streets too often if there is a bike lane and not enough if there is not. The recommendation for practice is to provide low-traffic routes wherever possible in bicycle networks, not to limit bicycle facilities on high-traffic streets. Networks with extensive low-traffic bicycle facilities are robust to misalignments between preferences and doses because they reduce both the likelihood and severity of excess (non-minimum) doses. Highlights: Distance/traffic exposure trade-offs are compared for route preferences and doses. Preferences and doses align when choosing among low-to-moderate traffic facilities. In many situations preferences will lead to minimum-dose route choices. High-traffic streets with or without bike lanes can lead to excess-dose choices. Extensive low-traffic routes reduce the likelihood and severity of excess doses.